2017
DOI: 10.1002/qj.3131
|View full text |Cite
|
Sign up to set email alerts
|

Scatterometer estimates of the tropical sea‐breeze circulation near Darwin, with comparison to regional models

Abstract: In tropical coastal environments, simulating the diurnal cycle of wind and precipitation in numerical weather and climate models presents unique challenges due to the interaction of intraseasonal and mesoscale dynamics. This can lead not only to incorrect short‐term weather forecasts but also to unphysical energy and momentum transport by convective processes. In particular, the sea/land‐breeze circulation and its role in initiating convection has been identified as a possible source of errors in the timing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…We omit the Seawinds evening minus morning winds because they do not show the sea breeze as clearly, due to the Seawinds observation times (10:30 and 22:30). Note that Brown et al () recently studied the land‐sea breeze off of northern Australia using evening minus morning winds, as measured by the Advanced Scatterometer (ASCAT), which makes observations at 9:30 and 21:30 local time.…”
Section: Methodsmentioning
confidence: 99%
“…We omit the Seawinds evening minus morning winds because they do not show the sea breeze as clearly, due to the Seawinds observation times (10:30 and 22:30). Note that Brown et al () recently studied the land‐sea breeze off of northern Australia using evening minus morning winds, as measured by the Advanced Scatterometer (ASCAT), which makes observations at 9:30 and 21:30 local time.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, there has been a focus on the interaction between intraseasonal variability and mesoscale effects forced by the steep topography and complex coastlines of the MC. Several studies have suggested that these mesoscale, coastally influenced processes are suppressed during periods of large-scale convection associated with the active phases of the Madden Julian Oscillation (MJO; e.g., Birch et al, 2016;Peatman et al, 2014;Vincent & Lane, 2017a), the Indo-Australian monsoon (Brown et al, 2017), or other intraseasonal events such as Kelvin waves or equatorial Rossby waves (Vincent et al, 2016). It follows that similar effects may be observed on longer time scales during the comparatively cloudy background conditions of La Niña seasons relative to El Niño seasons.…”
Section: Introductionmentioning
confidence: 99%
“…This has spurred efforts to perform high-resolution regional model simulations over the MC (Argüeso et al, 2016;Birch et al, 2016;Vincent & Lane, 2017a) with the aim of more accurately modeling atmospheric processes in the region. Several studies have suggested that these mesoscale, coastally influenced processes are suppressed during periods of large-scale convection associated with the active phases of the Madden Julian Oscillation (MJO; e.g., Birch et al, 2016;Peatman et al, 2014;Vincent & Lane, 2017a), the Indo-Australian monsoon (Brown et al, 2017), or other intraseasonal events such as Kelvin waves or equatorial Rossby waves (Vincent et al, 2016). In particular, there has been a focus on the interaction between intraseasonal variability and mesoscale effects forced by the steep topography and complex coastlines of the MC.…”
Section: Introductionmentioning
confidence: 99%
“…Such organised tropical convection also plays an essential role in global climates via its impacts on planetary circulations such as the Walker circulation or the Madden-Julian Oscillation (Hendon and Woodberry, 1993;Zhang, 2005). Given their importance, a number of efforts have been made to examine how different atmospheric or land-surface parameters modify tropical sea breeze convective systems (Qian et al, 2012;Grant and van den Heever, 2014;Bergemann and Jakob, 2016;Igel et al 2018;Park et al, 2020), as well as to improve their representation in numerical weather models (Boyle and Klein, 2010;Bergemann et al, 2017;Brown et al, 2017). However, in spite of these past studies, accurately predicting sea breeze convective systems remains challenging (Kidd et al, 2013;Azorin-Molina et al, 2014;Chen et al, 2015;Banta et al, 2020;Short, 2020).…”
Section: Introductionmentioning
confidence: 99%